Penggunaan Teknologi Artificial Intelligence (Ai) Pada Pengelolaan Sistem Pertanian Di Dusun Bentenu Gerung Lombok Barat - Djul Fikry; Misbahuddin Misbahuddin; M. Syamsu Iqbal; A. Sjamsjiar Rachman; Lalu Ahmad S. Irfan Akbar; Giri Wiriasto (Universitas Mataram, 2026)
This community service program aims to enhance the capacity of farmers in Bentenu Hamlet, West Lombok, in adopting Artificial Intelligence (AI) technology to support the transformation from traditional agriculture to digital-based smart farming. The main challenges faced by partners include low technological literacy, limited access to modern agricultural information, and reliance on conventional farming practices. The implementation methods consist of socialization, training, mentoring, and evaluation. Training materials cover the introduction of AI concepts, the use of the Plantix application for crop disease and pest diagnosis, the utilization of temperature, humidity, and soil pH sensors, as well as the introduction of Internet of Things (IoT)-based systems. The results show improved farmers’ understanding and skills in using digital technologies for land monitoring and decision-making in agricultural practices. Farmers are also able to identify plant problems more quickly and accurately using AI-based applications. Furthermore, the program increases farmers’ motivation to adopt modern technologies to improve agricultural productivity. Therefore, this activity contributes to enhancing digital literacy, improving agricultural efficiency, and accelerating the transition toward smart farming in rural areas